2017
DOI: 10.1016/j.jamcollsurg.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia after Hepatectomy or Pancreatectomy: Role of the Nicotinamide Phosphoribosyltransferase

Abstract: Background Postoperative hypophosphatemia is common and is associated with a lower risk of liver failure after hepatectomy but higher morbidity after pancreatectomy. Whether different physiologic mechanisms underlie the hypophosphatemia associated with these very different clinical outcomes is unclear. This study aims to evaluate the underlying mechanism in postoperative hypophosphatemia. Study designs We prospectively enrolled 120 patients who underwent major hepatectomy (n=30), minor hepatectomy (n=30), pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
(59 reference statements)
2
16
0
Order By: Relevance
“…5 However, the condition is also observed following surgical procedures. 13,14 The observation of hypophosphatemia following pancreatectomy in this study supports prior literature citing reports of postoperative hypophosphatemia in hepatectomy, colectomy, and gastrectomy patients. 14-17 Within these patient cohorts, severe hypophosphatemia was also associated with organ-specific complication incidence following gastrointestinal operations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…5 However, the condition is also observed following surgical procedures. 13,14 The observation of hypophosphatemia following pancreatectomy in this study supports prior literature citing reports of postoperative hypophosphatemia in hepatectomy, colectomy, and gastrectomy patients. 14-17 Within these patient cohorts, severe hypophosphatemia was also associated with organ-specific complication incidence following gastrointestinal operations.…”
Section: Discussionsupporting
confidence: 86%
“…13,14 The observation of hypophosphatemia following pancreatectomy in this study supports prior literature citing reports of postoperative hypophosphatemia in hepatectomy, colectomy, and gastrectomy patients. 14-17 Within these patient cohorts, severe hypophosphatemia was also associated with organ-specific complication incidence following gastrointestinal operations. 3,18 Because of the prevalence of hypophosphatemia postoperatively, it may be important to determine if complication incidence is associated with the severity of hypophosphatemia.…”
Section: Discussionsupporting
confidence: 86%
“…Elegant work has demonstrated that the nicotinamide phosphoribosyl transferase (Nampt)/ (NAD + ) intracellular pathway plays a fundamentally important role in the expression of renal and intestinal phosphate transporters (NaPi-2a, NaPi-2b, and NaPi-2c), and likely plays an additional role in the transcellular shifts from other organs that occur independent of oral phosphate ingestion, and which determine diurnal variation in serum phosphate concentration. [25][26][27] Even our understanding of what constitutes a "phosphate-restricted diet" is now known to be on the basis of basic misunderstandings about the relative contribution of animal-versus plant-versus additive-based phosphate exposure. 9,28 Our findings here indicate a clear and substantial contribution of paracellular phosphate transport to net phosphate absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Although dextrose may cause transcellular shift of phosphate, this shift would be transient. In a prospective cohort study, the authors found postoperative hypophosphatemia was related to hyperphosphaturia, as likely mediated by nicotinamide phosphoribosyltransferase (NAMPT), which acted as a phosphaturic factor as well as a metabolic enzyme that synthesizes nicotinamide adenine dinucleotides [34,35], The role of NAMPT on OSC was not studied and it warrants additional investigation. Furthermore, whether hypophosphatemia is the symptom or cause of complication is also unclear.…”
Section: Discussionmentioning
confidence: 99%